2012
DOI: 10.1016/j.ijmecsci.2012.02.001
|View full text |Cite
|
Sign up to set email alerts
|

Buckling patterns of complete spherical shells filled with an elastic medium under external pressure

Abstract: The critical buckling characteristics of hydrostatically pressurized complete spherical shells filled with an elastic medium are demonstrated. A model based on small deflection thin shell theory, the equations of which are solved in conjunction with variational principles, is presented. In the exact formulation, axisymmetric and inextensional assumptions are not used initially and the elastic medium is modelled as a Winkler foundation, i.e. using uncoupled radial springs with a constant foundation modulus that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
7
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…If the pressure increases beyond a certain limit, the spherical equilibrium form of the compressed shell may become unstable and buckling occurs [33]. As described before, the axisymmetric assumption has little effect on the calculated values of the critical buckling pressure and the corresponding buckling mode number [34]. Thus, it is assumed that the buckling deformation is axisymmetric with respect to the vertical axis in order to simplify the calculation of the critical pressure.…”
Section: Buckling Of Uniform Pressurised Spherical Shellsmentioning
confidence: 99%
See 2 more Smart Citations
“…If the pressure increases beyond a certain limit, the spherical equilibrium form of the compressed shell may become unstable and buckling occurs [33]. As described before, the axisymmetric assumption has little effect on the calculated values of the critical buckling pressure and the corresponding buckling mode number [34]. Thus, it is assumed that the buckling deformation is axisymmetric with respect to the vertical axis in order to simplify the calculation of the critical pressure.…”
Section: Buckling Of Uniform Pressurised Spherical Shellsmentioning
confidence: 99%
“…These works show that the approximate formulations enable sufficiently accurate values of the critical buckling pressure and the corresponding buckling mode number to be obtained. It can also be inferred from the work of Sato et al [34] that when ⁄ <10 -3 ( is the core radius; is the core foundation modulus; and is the shell Young's modulus), the buckling behaviours of the shell filled with elastic materials is the same as that for the empty shell.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…They proposed an intriguing idea that the shapes of many natural fruits and vegetables can be reproduced by anisotropic stress-driven buckling on the spheroidal core/shell system. The role of internal core on the spherical shell buckling was also considered by Sato et al [8]; they derived analytic solutions for the buckling pressures and patterns of a complete spherical shell filled with an elastic medium (Winkler foundations) using exact formulations. Their formulation clearly showed that the interaction between shells and Winkler foundations causes only axisymmetric buckling modes and that no non-axisymmetric modes can occur.…”
Section: Introductionmentioning
confidence: 99%
“…Bich and Tung 6 investigated the Non-linear axisymmetric response of functionally graded shallow spherical shells under uniform external pressure including temperature effects. The Nonlinear static and dynamic buckling analysis of functionally graded shallow spherical shells including temperature effects are studied by Bich et al 7 The buckling patterns of complete spherical shells filled with an elastic medium under external pressure is investigated by Sato et al 8 Some authors have recently demonstrated the cross-sectional morphology of * Author to whom correspondence should be addressed. carbon nanotubes embedded in an elastic medium.…”
Section: Introductionmentioning
confidence: 99%